An Investigation into Capacitive Performances and Impedance Contributions Due to Structural Differences of Biochar Thin Film and Monolith Supercapacitor Electrodes. (7th July 2017) - Yanchus, Daniel; Kirk, Donald W.; Jia, Charles Q.
Abstract : This study investigates biochar supercapacitor electrodes made several times larger than the status quo, using both monolithic and thin film structures. Slow-pyrolysis of wood precursors produces biochar carbon monoliths which retain the internal structures of biomass. While this natural network of transportation channels for water and nutrients was not found to facilitate ion migration in capacitive charge/discharge cycles, monolithic electrodes revealed lower intrinsic resistances than thin films containing PTFE binder. As a consequence, monolithic electrodes up to 5 mm thick show equivalent specific capacitance performance to their thin film counterparts.